Hospital Preparedness, Resilience, and Psychological Burden Among Clinical Nurses in Addressing the COVID-19 Crisis in Riyadh, Saudi Arabia - Balay-odao, Ejercito Mangawa; Alquwez, Nahed; Inocian, Ergie Pepito; Alotaibi, Raid Salman (Frontiers in Public Health, 2021)
In the continuous effort to minimize the devastating effects of coronavirus disease (COVID-19) and to curb the spread of the disease, hospital preparedness and resilience play significant roles in the psychological well-being of clinical nurses given that their work demands immediate action to adapt and adjust to stressors. Thus, this study investigates the hospital preparedness, psychological burden, and resilience of clinical nurses in addressing COVID-19 in Riyadh, Saudi Arabia. A total of 281 clinical nurses participated in the survey from April 2020 to June 2020. Results show that clinical nurses perceived a high self-assessed COVID-19 hospital preparedness (49.65, SD=2.30); high self-assessed nurses’ resilience (4.03, SD=0.36); and most have normal levels of depression, anxiety, and stress. The variables were predicted to be statistically significant (F18, 262 = 4.14, p .001) and accounted for 16.8% of the variance in the nurses’ perception of hospital preparedness (R2=0.221; adjusted R2=0.168). The regression analysis was statistically significant (F30, 250 = 6.71, p .001) and accounted for 38% of the variance in nurses’ resilience (R2 = 0.446, Adjusted R2 = 0.380). The predictors of depression, anxiety, and stress show that the overall relationship was statistically significant at (F23, 257 = 6.71, p .000), (F23, 257 = 6.675, p .000), and (F23, 257 = 6.692, p .000) with 31.9% of the variance (R2 = 0.375, Adjusted R2 = 0.319), 31.8% of the variance (R2 = 0.374, Adjusted R2 = 0.318), and 31.9 % of the variance (R2 = 0.375, Adjusted R2 = 0.319), respectively. The findings of this study helps in improving the continuing education program, psychological support, and mental health program to ensure that the needs of clinical nurses are addressed during the outbreak of a disease.